Effect of pin-fin forms on flow and cooling characteristics of three-layer porous laminate. (25th July 2021) - Zhang, J.; Han, H.Z.; Li, Z.R.; Zhong, H.G.
Highlights: An engineering scale experiment was conducted on a new three-layer porous laminate. The flow and heat transfer of two- and three-layer porous laminate were compared. Cylindrical, truncated cone, square and hexagonal pin-fins were compared. The performance evaluation criteria of square pin–fin was superior to other forms. An empirical correlations of four types of pin–fin heat transfer were fitted. Abstract: Pin-fin can promote heat transfer by increasing the effective heat transfer area and enhancing turbulence intensity. In this study, engineering scale comparative experiments between two- and three-layer porous laminates with the same pin-fins were examined to determine the differences in flow and cooling characteristics. Using the three-layer porous laminates, the effects of four types of pin–fin forms (cylindrical, truncated cone-shaped, square and hexagonal) on flow and cooling characteristics were comparatively researched, with Reynolds numbers ranging from 3, 300 to 6, 200. The results indicated that the heat transfer coefficient of the square pin–fin was 27.15%, 42.11%, and 19.84% higher than those of the cylindrical pin–fin, truncated cone-shaped pin–fin and hexagonal pin–fin, respectively. The cooling efficiency of the square pin–fin was 1.77%, 2.60%, and 1.18% higher than those of the cylindrical pin–fin, truncated cone-shaped pin–fin and hexagonal pin–fin, respectively. The performance evaluation criteria of the square pin–fin were superior to those of the other structures with the same consumption of pumping power. Empirical correlations of the Nusselt number and cooling efficiency of the four pin–fin forms of the three-layer porous laminate were obtained with prediction errors less than 15.00% and 0.3%, respectively.